2017
DOI: 10.1590/s0100-736x2017000800013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Kalanchoe gastonis-bonnieri extract to control bacterial biofilms and dental calculus in dogs

Abstract: RESUMO.-[Eficácia do extrato de Kalanchoe gastonis--bonnieri no controle do biofilme bacteriano e cálculo dentário em cães.] Um extrato aquoso de folhas da espé-cie medicinal Kalanchoe gastonis-bonnieri (aqui denominado como KGB) foi efetivo como um agente antimicrobiano contra as bactérias da cavidade oral de cães em testes in vitro. Neste estudo, investigou-se o efeito da administração oral tópica de KGB sobre o desenvolvimento do biofilme dental em cães da raça Beagle. Os experimentos foram realizados com u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
4
0
4
Order By: Relevance
“…Assim, a progressão da formação do biofilme dentário induz diversas alterações no equilíbrio microbiano, podendo originar a placa dentária, formada por agregados de bactérias e seus subprodutos, componentes salivares, detritos orais e células epiteliais e inflamatórias ocasionais (Riggio et al, 2011;Whyte et al, 2014). A placa dentária, por sua vez, favorece o desenvolvimento da doença periodontal (PD), identificada como a ocorrência clínica mais comum em cães domésticos (Abdalla et al, 2017;Kyllar & Witter, 2005). A formação do biofilme ocorre quase imediatamente após um procedimento profissional de limpeza dos dentes.…”
Section: Introductionunclassified
“…Assim, a progressão da formação do biofilme dentário induz diversas alterações no equilíbrio microbiano, podendo originar a placa dentária, formada por agregados de bactérias e seus subprodutos, componentes salivares, detritos orais e células epiteliais e inflamatórias ocasionais (Riggio et al, 2011;Whyte et al, 2014). A placa dentária, por sua vez, favorece o desenvolvimento da doença periodontal (PD), identificada como a ocorrência clínica mais comum em cães domésticos (Abdalla et al, 2017;Kyllar & Witter, 2005). A formação do biofilme ocorre quase imediatamente após um procedimento profissional de limpeza dos dentes.…”
Section: Introductionunclassified
“…1 The use of physical methods (such as regular tooth brushing, and provision of abrasive foods and toys) together with chemical methods (such as oral antiseptic-containing dentifrices) should be considered as a critical measure for microbial burden reduction and to control proliferation and establishment of these microbial colonies. [5][6][7][8] Solutions, creams, pastes, gels, and foams are the most commonly encountered pharmaceutical dosage forms for use in toothpastes or mouthwashes for the oral cavity. 1,7,8 However, the exposure time of the oral mucosa to the drugs in these products is short, whether due to the washing and rinsing process, or the presence of a continuous salivary flow and the mechanical movements of the mouth and tongue.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds such as copaiba oil, clove essential oil, aloe extract, palm beachbells extract, guava extract, green tea extract, and pomegranate peel extract have been studied. 5,[15][16][17] According to Bolzan (2018), the natural oral microbiota of Labrador dogs was sensitive to various plant extracts, including the hydroalcoholic extracts of pomegranate peels that produced inhibition halos at all tested concentrations (5.0 to 250.0 mg/mL). 18 Ensuring proper dental homecare is one of the fundamental measures that owners can take for the maintenance of oral health in dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we reported the isolation of the new flavonoid quercetin 3- O - α -rhamnopyranoside-7- O - β -D-glucopyranosyl-(1→3)- α -L-rhamnopyranoside, as well as vicenin-2, a C -glycosyl flavone, from the leaf extract of KGB [26]. We also demonstrated that aqueous extracts from K. gastonis-bonnieri (KGB) are effective in controling dental bacterial plaque and calculus in dogs [27].…”
Section: Introductionmentioning
confidence: 99%